Depressive Symptomatology and College Persistence among African American College Students. Issue 2 (2nd April 2016) - Boyraz, Güler; Horne, Sharon G.; Owens, Archandria C.; Armstrong, Aisha P.
ABSTRACT: The purpose of this study was to examine the relationship between depressive symptomatology and college outcomes among African American students, as well as to determine whether these relationships were moderated by gender and type of university. Participants included 569 African American first-year students attending two public universities in the Southeast United States: a historically Black college/university (HBCU) and a predominantly White institution (PWI). Using a longitudinal study design, data were collected at three time points. Results indicated that, after adjusting for the effects of the control variables (gender, type of institution, high school GPA, participation in on-campus activities, institutional and goal commitments), depressive symptomatology present in the first semester of college was associated with increased likelihood of dropping out of college before the end of the second year of college. The relationship between these two variables was mediated by first-year cumulative GPA. Results also indicated that the hypothesized relationships did not vary as a function of gender and the university type.